Market Basket And Time Series Analysis: Case Study PT XYZ Sales Data - Muhammad Wildan; Moh Thaha Rizieq Hentihu; Riyanto Jayadi (Publikasi Indonesia, 2025)
PT. XYZ is a retail company that has been operating since 2015 in New York, which seeks to increase sales through attractive package bidding strategies and ensuring stock availability for the following month's highest-selling items. The project aims to analyze and forecast the items that will have the highest sales as well as provide package recommendations that can increase sales. The analysis was carried out using a machine learning model, with the Market Basket Analysis (MBA) method for package recommendations and the Auto Regressive Integrated Moving Average (ARIMA) for sales predictions. The results of the analysis show that the